Radioresistant mouse pheochromocytoma cell lines - Lemm, Sandy; Gebhardt, Marcel; Groß, Thomas; Richter, Susan; Ullrich, Martin; Pietzsch, Jens (Frontiers in Oncology, 2025)
ObjectivePatients diagnosed with metastatic pheochromocytoma/paraganglioma (PCC/PGL) have limited treatment options. In some cases, peptide receptor radionuclide therapy (PRRT) is followed by an eruption of metastases, possibly originating from tumor cells with a radioresistant phenotype. However, the underlying mechanisms of radioresistance in PCC/PGL remain largely unknown and appropriate models are missing.MethodsTwo genetically modified mouse pheochromocytoma (MPC) cell lines, one positive and one negative for hypoxia-inducible factor 2α expression (MPC+HIF-2α and MPC+EV [empty vector], respectively), were X-ray-conditioned through fractionated irradiation at sublethal doses. Two procedures were tested: one allowed for recovery between each irradiation step (recIR), while the other demanded daily irradiation (dayIR). Changes in cell morphology, growth rates, and DNA repair (γH2AX immunostaining) were characterized in response to irradiation.ResultsWe generated two MPC+HIF-2α- and two MPC+EV-derived cell lines that tolerate irradiations with X-rays at dose fractions of 2 Gy per day without significant growth inhibition. All recIR-and dayIR-conditioned cell lines showed increased DNA repair capacity. Morphological changes toward stronger clustering and slower growth were more pronounced in dayIR-conditioned than in recIR-conditioned cell lines. X-ray-conditioned MPC+HIF-2α cells showed the highest increase in resistance to X-ray-treatment with dose fractions up to 5 Gy per day.ConclusionThe herein established X-ray-conditioned MPC cell lines represent PCC/PGL models with a radioresistant phenotype. Further investigations on the radiation-induced genetic responses of these cell lines, their corresponding tumor spheroids, and tumor allografts in mice will help to elucidate the underlying mechanisms of acquired radioresistance and radionuclide therapy-induced metastatic eruption in PCC/PGL. Lastly, the suitability of advanced PRRT and complementary treatments can be tested to improve theranostic strategies.